The pathogenic role of dendritic cells in non-infectious anterior uveitis. (August 2018) - O'Rourke, M.; Fearon, U.; Sweeney, C.M.; Basdeo, S.A.; Fletcher, J.M.; Murphy, C.C.; Canavan, M.
Abstract: Background: Anterior uveitis (AU) is characterised by infiltration of immune cells into the anterior chamber of the eye. Dendritic cells (DC) are professional antigen presenting cells that initiate and promote inflammation. This study aims to characterise DC in AU and to examine the effects of aqueous humor (AqH) on DC maturation and function. Methods: The frequency and phenotype of AU and healthy control (HC) circulating DC was examined. AU and HC AqH was immunostained and assessed by flow cytometry. The effect of AU and HC AqH on DC activation and maturation was examined and subsequent effects on CD4 + T cell proliferation assessed. Results: AU peripheral blood demonstrated decreased circulating myeloid and plasmacytoid DC. Within AU AqH, three populations of CD45 + cells were significantly enriched compared to HC; DCs (CD11c + HLA-DR + ), neutrophils (CD15 + CD11c + ) and T cells (CD4 + and CD8 + ). A significant increase in IFNγ, IL8 and IL6 was observed in the AU AqH, which was also significantly higher than that of paired serum. AU AqH induced expression of CD40 and CD80 on DC, which resulted in increased T cell proliferation and the production of GM-CSF, IFNγ and TNFα. Conclusion: DC are enriched at the site of inflammation in AU. Our data demonstrate an increase in inflammatory mediators in the AU inflamed microenvironment. AU AqH can activate DC, leading to subsequent proliferation and activation of effector T cells. Thus, the AU microenvironment contributes to immune cell responses and intraocular inflammation. Highlights: DC are initiations of inflammation being involved in the unique immune deviation properties of the eye. This study analysed DC in circulation and locally in AU patients and examined the effects of AqH on a DC model. AU patients have decreased circulating DC. APCs, neutrophils and T cells are present in the inflamed anterior chamber during AU. AU AqH can activate a DC model with subsequent activation of T cells through the effect of released soluble mediators. This study supports a role of DC in the pathogenesis of AU. Abstract : The anterior chamber in anterior uveitis (AU) patients contains inflammatory type dendritic cells (DC). AU aqueous humor activates DC, which subsequently activate effector T cells suggesting a role for DC in the pathogenesis of AU.